Low cost foam-gelcasting preparation and characterization of porous magnesium aluminate spinel (MgAl2O4) ceramics. Issue 16 (December 2016) - Deng, Xiangong; Wang, Junkai; Liu, Jianghao; Zhang, Haijun; Han, Lei; Zhang, Shaowei
Abstract: Porous MgAl2 O4 ceramics were prepared via a low cost foam-gelcasting route using MgAl2 O4 powders as the main raw material, ammonium polyacrylate as a dispersant, a small amount of modified carboxymethyl cellulose as a gelling agent, and TH-IV polymer as a foaming agent. The effects of additive's content, solid loading and gelling temperature on slurry's rheological behavior were investigated, and microstructures and properties of as-prepared porous MgAl2 O4 ceramics examined. Based on the results, the roles played by the foaming agent in the cases of porosity, pore structure, pore size, mechanical properties and thermal conductivity were clarified. Porosity and pore sizes of as-prepared porous MgAl2 O4 ceramics increased with increasing the foaming agent from 0.05 to 0.6 vol%. Porous MgAl2 O4 ceramics with porosity of 75.1% and average pore size of 266 µm exhibited a compressive strength as high as 12.5±0.8 MPa and thermal conductivity as low as 0.24 W/(m K) (at 473 K).